2009
DOI: 10.1590/s1516-31802009000600012
|View full text |Cite
|
Sign up to set email alerts
|

Nonfunctional parathyroid cyst: case report

Abstract: CONTEXT: Parathyroid cysts are rare clinical and pathological entities, with less than 300 cases reported. The inferior parathyroid glands are most commonly involved, with left-side predominance. Parathyroid cysts may be functional or nonfunctional, depending on their association with hypercalcemia. CASE REPORT:A 25-year-old man presented a palpable asymptomatic left-side neck mass. Ultrasound revealed a cystic structure contiguous with the left thyroid lobe. Serum ionic calcium was normal. The patient underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This technique was especially used in case of a recurrence of PCs after FNA in order that open surgery is avoided. [ 17 , 172 , 200 , 212 , 214 ] In the literature, there are several reports of sclerotherapy with tetracycline or ethanol injection used as treatment of PCs, especially in nonfunctioning ones. [ 170 , 178 , 217 219 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique was especially used in case of a recurrence of PCs after FNA in order that open surgery is avoided. [ 17 , 172 , 200 , 212 , 214 ] In the literature, there are several reports of sclerotherapy with tetracycline or ethanol injection used as treatment of PCs, especially in nonfunctioning ones. [ 170 , 178 , 217 219 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 200 ] After surgical excision of PCs, hypocalcemia, hypercalcemic crisis, hemorrhage, and recurrent laryngeal nerve palsy have been referred as postoperative complications. [ 18 , 65 , 172 , 195 ] Neck pain and neurotoxicity leading to recurrent laryngeal nerve palsy seem to have an association with sclerotherapy. [ 172 , 210 ]…”
Section: Discussionmentioning
confidence: 99%
“…[1,3,7,9] It has been reported that ultrasound, computerized tomography or magnetic resonance imaging may be helpful in discriminating solid/cystic cervical masses and showing their anatomical relation, and that thyroid scintigraphy may be helpful in revealing the presence of non-functional cysts, however none of these imaging methods can discriminate the thyroid/parathyroid origin of the lesions. [1,3,[7][8][9] In physical examination, PCs are soft, mobile masses. They have a semitransparent thin wall with smooth and shiny surface, that can easily be dissected from the thyroid tissue and surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…1 So far, approximately 300 cases have been reported in the literature. 2,3 Parathyroid cysts are categorized as functioning and nonfunctioning depending on their ability to secrete parathyroid hormone (PTH). 4 Parathyroid cysts are mostly nonfunctional with nonspecific physical and radiological characteristics.…”
Section: Introductionmentioning
confidence: 99%